2020
DOI: 10.2196/preprints.23684
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Indian Clinical Trials on COVID-19: A Review of Clinical Trials Registry of India (CTRI) (Preprint)

Abstract: BACKGROUND The COVID-19 has impacted the world in an unprecedented way. More than 200 countries have been affected because of this novel coronavirus. Global public health, economy and society have all faced near breakdown. There is a surge for identifying vaccine or repurposing existing drugs for this virus. OBJECTIVE An attempt has been made to provide a comprehensive overview on clinical tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Approximately 35% of the registered trials in the CTRI for COVID were for indigenous systems of medicine in India, i.e., AYUSH and associated therapies, and held the majority chunk of the registered studies in the CTRI. An analysis conducted by Raju et al reported a similar proportion (35%) for the AYUSH studies [20]. An early study by Charan et al reported a higher proportion (61.5%) as compared to the present analysis [16].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Approximately 35% of the registered trials in the CTRI for COVID were for indigenous systems of medicine in India, i.e., AYUSH and associated therapies, and held the majority chunk of the registered studies in the CTRI. An analysis conducted by Raju et al reported a similar proportion (35%) for the AYUSH studies [20]. An early study by Charan et al reported a higher proportion (61.5%) as compared to the present analysis [16].…”
Section: Discussionsupporting
confidence: 61%
“…A similar study reported Guduchi, ashwagandha, Yashtimadhu, AYUSH-64, AYUSH Kwath, curcumin, and chyawanprash as the common interventions used for COVID [25]. Raju et al reported a lower proportion (25%) of trials of COVID-19 registered with Ayurveda and yoga therapies [20].…”
Section: Discussionmentioning
confidence: 87%
“…The generalization and representativeness of the study findings may also be limited due to the use of convenience sampling and web-based data collection procedures. Although online surveys might only reach a selected population (those who have access to the Internet and are highly educated), they also allow for a fast and easy access to a large population within a wide geographic area (Vasantha Raju & Harinarayana, 2016). We have indeed reached an adequate number of participants, which provided good statistical power and the possibility to compare subgroups.…”
Section: Study Limitationsmentioning
confidence: 93%
“…We conducted a cross-sectional online pilot study using online Google forms, which is a freely available cloud-based data management tool for online surveys (Vasantha Raju & Harinarayana, 2016). As the study was conducted during SARS-CoV 2 pandemic, digital research was considered as the most appropriate methodology (Favilla & Pita, 2020).…”
Section: Methodsmentioning
confidence: 99%